(11*11-1)/5=24
(2*5-7)*8=24
6/(5/4-1)=24
1: (11 × 11 - 1) ÷ 5
2: ((11 × 11) - 1) ÷ 5]
1: 8 × (5 × 2 - 7)
2: 8 × ((5 × 2) - 7)
3: 8 × (2 × 5 - 7)
4: 8 × ((2 × 5) - 7)
5: (5 × 2 - 7) × 8
6: ((5 × 2) - 7) × 8
7: (2 × 5 - 7) × 8
8: ((2 × 5) - 7) × 8
1: 6 ÷ (5 ÷ 4 - 1)
2: 6 ÷ ((5 ÷ 4) - 1)
3: 4 ÷ (1 - 5 ÷ 6)
4: 4 ÷ (1 - (5 ÷ 6))
1) (11×11-1)÷5=24
(2) (2×5-7)×8=24
(3) 4 ÷ (1 - 5 ÷ 6)=24
4 ÷ (1 - (5 ÷ 6))=24
6 ÷ (5 ÷ 4 - 1)=24
6 ÷ ((5 ÷ 4) - 1)=24
我这个是对的
11,11,1,5
8,5,2,7
1,4,5,6
好象都不行
(11*11-1)/5=24
(2*5-7)*8=24
6/(5/4-1)=24
相信我,没错。
1: (11 × 11 - 1) ÷ 5
2: ((11 × 11) - 1) ÷ 5]
1: 8 × (5 × 2 - 7)
2: 8 × ((5 × 2) - 7)
3: 8 × (2 × 5 - 7)
4: 8 × ((2 × 5) - 7)
5: (5 × 2 - 7) × 8
6: ((5 × 2) - 7) × 8
7: (2 × 5 - 7) × 8
8: ((2 × 5) - 7) × 8
1: 6 ÷ (5 ÷ 4 - 1)
2: 6 ÷ ((5 ÷ 4) - 1)
3: 4 ÷ (1 - 5 ÷ 6)
4: 4 ÷ (1 - (5 ÷ 6))
相信我